Case report of cadaveric kidney transplantation with renal-portal venous drainage: A feasible way for a venous drainage in a complex generalized thrombosed vessels setting. (2016) - Millan, Mauricio; Caicedo, Luis A.; Villegas, Jorge I.; Serrano, Oscar; Caicedo, Liliana; Duque, Mauricio; Thomas, Laura S.; Echeverri, Gabriel J.
Highlights: One of the frequent complications suffered by patients with chronic renal failure is the lack of vascular access due to venous thrombosis. Patients with vascular structural alteration are technicaly challenging. Kidney transplant with portal venous drainage is an alternative in a general thrombosed vessels setting. The implant of the renal graft was undertaken via an anastomosis at the lateral side of the renal vein to the portal vein. Abstract: Introduction: One of the frequent complications suffered by patients with chronic renal failure is the lack of vascular access due to venous thrombosis. This means that the transplant surgeon must have a detailed knowledge of the intra-abdominal venous system, and other alternative surgeries, at the time of performing the renal graft implant, in order to ensure a good venous drainage. Presentation of the case: This article provides a case report regarding a patient with no vascular access and with surgical difficulties at the time of the kidney transplant, in whom a renal-portal venous drainage was performed with very good outcome. Discusion: Renal-portal venous drainage is a way to performe kidney transplant with good outcome. In Fundación Valle del Lili we have overcome the lack of vascular access in patients that need a renal transplant by new surgical technics that improve the patients quality of life and survival. Conclusion: We can conclude that new surgical alternatives exist for those patients with chronic renal failure that have no vascular access. These patients are a priority for kidney transplants and the surgeon must take in to account the need for a new surgical assessment.